Annotazioni sul testo del Salmo 17 - Bazyliński, Stanisław (The Biblical Annals, 2021)
On the basis of the Hebrew manuscripts and other ancient textual witnesses, this article singles out and discusses many text-critical and translational issues regarding Psalm 17, dwelling particularly upon vv.11 and 14. For v.11, the author accepts the conjectural reading אִשְּׁרוּנִי עתַָּה סְבָבוּנִ י , “they have advanced/moved against me, now, they have encircled me”. For v.14, the author gives preference to the qere וּצְפוּנְךָ with the collective meaning: “and your protected ones”.